Role of intermediate phase for stable cycling of Na7V4(P2O7)(4)PO4 in sodium ion battery - Lim, Soo Yeon; Kim, Heejin; Chung, Jaehoon; Lee, Ji Hoon; Kim, Byung Gon; Choi, Jeon-Jin; Chung, Kyung Yoon; Cho, Woosuk; Kim, Seung-Joo; Goddard, William A., III; Jung, Yousung; Choi, Jang Wook (NATL ACAD SCIENCES, 2014)
Sodium ion batteries offer promising opportunities in emerging utility grid applications because of the low cost of raw materials, yet low energy density and limited cycle life remain critical drawbacks in their electrochemical operations. Herein, we report a vanadium-based ortho-diphosphate, Na7V4(P2O7)(4)PO4, or VODP, that significantly reduces all these drawbacks. Indeed, VODP exhibits single-valued voltage plateaus at 3.88 V vs. Na/Na+ while retaining substantial capacity (> 78%) over 1,000 cycles. Electronic structure calculations reveal that the remarkable single plateau and cycle life originate from an intermediate phase (a very shallow voltage step) that is similar both in the energy level and lattice parameters to those of fully intercalated and deintercalated states. We propose a theoretical scheme in which the reaction barrier that arises from lattice mismatches can be evaluated by using a simple energetic consideration, suggesting that the presence of intermediate phases is beneficial for cell kinetics by buffering the differences in lattice parameters between initial and final phases. We expect these insights into the role of intermediate phases found for VODP hold in general and thus provide a helpful guideline in the further understanding and design of battery materials.
Keywords: PYROPHOSPHATE CATHODE; ELECTRODE MATERIALS; POSITIVE-ELECTRODE; CRYSTAL-STRUCTURE; AB-INITIO; NA; STABILITY; INTERCALATION; STRAIN; OXIDE